Age and weight at first conception and calving in inter-se Jersey x Kankrej heifers - TRIVEDI, M M; PATEL, J M (The Indian Journal of Animal Reproduction, 2023)
The age and weight at first conception and calving were recorded in 24 inter-se Jersey x Kankrej heifers fed individuallyfor energy and protein requirements as per Sen et al. (1978) feeding standard. The age and weight at first conception were586.91±0.28 days and 264.00±6.44 kg, respectively. The corresponding values at first calving were 867.65±10.43 days and341.06±9.02 kg. Significant positive correlations were found between weight at different ages and weight at conception as well ascalving and between later two traits too. The results indicated that individual care and standard feeding in inter-se heifers could reduceage at first conception and calving.
Keywords: Age and weight; first conception; first calving; Jersey x Kankrej inter-se heifers